A new creative Kurdish constitution in the Middle East - Radpey, Loqman; Rose, Gregory (Creativity Studies, 2017)
The uprising in Syria since 2011 has created opportunities for creative approaches to Kurdish self-rule. The decision of Bashar al-Assad’s armed forces to withdraw from Kurdish cities in Northern Syria enabled Kurdish parties to take charge of local state institutions, declare self-rule, and to replace Syria’s flags with their own. The Democratic Union Party (Syria) announced a new constitution on 21 July 2013 that it called a “social contract”. On the basis of that constitution, Kurdish autonomous self-rule was formed comprising of three initial cantons. The principle of equality of all groups and the renunciation of the nation-state are revolutionary dimensions of the new constitution. In this paper, the new constitution’s creative dimensions are described and analyzed using a descriptive-analytic approach. The study aims to describe the articles of the constitution to analyze how minority Yazidis, Armenians, Arabs, Christians, Chechens, and Kurds might promote this model for the rest of Syria as a form of “democratic federalism”.Naujoji kūrybinė kurdų konstitucija Viduriniuosiuose RytuoseSantrauka. Sudėtingi Sirijos sukilimo (2011) įvykiai pastaruoju metu kurdams suteikė galimybę paskelbti savivaldą Šiaurės Sirijoje. Basharo al-Assado ginkluotų- jų pajėgų sprendimas atsitraukti nuo kurdų miestų leido kurdų partijoms perimti savo žinion vietines valstybines institucijas, įvesti savivaldą ir pakeisti Sirijos vėliavas savosiomis. Įvykus 2011 metų sukilimui, Sirijos kurdai įsteigė autonomiją de facto, o Demokratų są jungos partija (Sirija) 2013 m. liepos 21 d. paskelbė naują konstituciją, vadinamą visuomenine sutartimi. Ja remiantis buvo suformuota kurdų autonominė savivalda ir sudaryti trys kantonai – tai Jazira, Kobani ir Afrinas. Ketvirtasis kantonas buvo paskelbtas 2015 m. birželį – tai Tell Abjadas (kurd. Girê Spî). Pačiame karo įkarštyje bandyta imtis kai kurių naujų veiksmų, remiantis visų grupių lygybės principu. Nacionalinės valstybės atsisakymas – tai vienas iš revoliucinių ir kūrybinių aspektų. Jazidai, Armėnijos arabai, krikščionys, čečėnai ir kurdai viliasi, kad jų „demokratinio federalizmo“ veiksmai gali būti pavyzdys likusiai Sirijos daliai.Reikšminiai žodžiai: konstitucija, kūrybingumas, kurdai, Rojava, visuomeninė sutartis, Sirija.First published online: 13 Jan 2017